(untitled) (Practitioner Research, 2020)
This action research investigated the use of games to boost ESL rural primary pupils’ motivation to learn English vocabulary.18 Year 6 pupils from a rural school in Gua Musang Kelantan were selected by using convenient sampling. Multiple methods such as pre–test, post–test, observation, and interviews with teachers and pupils were used for data collection. This paper highlighted pupils’ voices of the effectiveness of vocabulary learning as the result of the pre and post-test showed a significant difference in which pupils have acquired the new words effectively and there was an improvement after having a game-based lesson. The findings indicated that the pupils showed significant improvement in their vocabulary scores after using games. Students reported that learning vocabulary by using games was fun and interesting, as it increased their motivation to learn the English language, helped them to memorise the vocabulary items faster, and increased their interaction in class. Furthermore, the competitive and repetitive nature of the game helped in vocabulary retention.